High-throughput in-silico screening of oxygen carrier candidates for chemical looping oxygen uncoupling -Thermodynamical and practical considerations of data mining from ab-initio databases — towards a cost-effective negative emission technology - Rehnberg, Viktor (My University, 2020)
It is clear that different techniques of carbon capture and storage will prove to be important in achieving the current global climate goals. One such technique is combustion of biofuel with chemical looping combustion or chemical looping oxygen uncoupling (CLOU). These are techniques where a metal oxide is used as an intermediary to transport oxygen between a chamber with an air inlet to a chamber with a fuel inlet. In CLOU the metal oxide is oxidised in the air chamber and then transports the extra oxygen to the fuel chamber. Thanks to the low partial pressure of oxygen in the fuel chamber the metal oxide is reduced and releases the extra oxygen. This oxygen in gaseous state will then react with the fuel and thus the partial oxygen pressure in the fuel chamber remain low. The metal oxide can continue looping through the two chambers transporting oxygen. As only oxygen and fuel are present in the combustion the only exhaust gases under full combustion are carbon dioxide and water. No toxic oxides of nitrogen are produced and expensive post-combustion gas separation of nitrogen and other flue gases can be avoided. The water can easily be separated by condensation and the carbon dioxide can then be captured cheaply and later stored in, for instance, geological formations underground. This report proposes a new method based on using the bountiful data from abinitio databases, for instance available in the Open Quantum Materials Database, to propose possible candidates for oxygen carriers in chemical looping oxygen uncoupling (CLOU). The data, in this case formation energy at 0K and 0Pa, is extrapolated based on thermodynamic considerations to find the stable phases of oxygen carriers under realistic conditions used for CLOU. Further considered criteria include mainly cost, toxicity and oxygen transfer capacity. A quantitative summary of all the considered criteria is proposed and also used to list potential metal oxide oxygen carriers in the order of how promising they seem for CLOU. The list can be used to guide what experimental investigations should prioritise, thus, it has the potential to significantly speed up the search for better oxygen carriers.
Keywords: chemical looping; material screening; data mining; Ellingham diagram; thermodynamics